The Medical Somatic Dissociation Questionnaire Assessment For Childhood Sexual Abuse: A Brief Report. Issue 2 (17th February 2023) - Balla, Uri; Lev-Wiesel, Rachel; Bhattacharyya, Atreyee; Israeli, David; Daphna-Tekoah, Shir
ABSTRACT: Child sexual abuse is a prevalent phenomenon worldwide. However, a gap exists between its incidence and its disclosure rate. Furthermore, assessment tools and techniques capable to identify the source of symptoms are lacking. This study investigates the extent to which the validated Medical Somatic Dissociation Questionnaire (MSDQ) can differentiate between sexually and non-sexually abused children. A total of 794 children and youth between the ages of 8 and 18 (mean age: 12.2 (SD = 2.3); 42% female, 58% male) were recruited from the general population; other participants were residents of boarding schools and children who were referred to medical treatment. The anonymous online questionnaire included queries about demographics, a condensed version of the Traumatic Life Events Questionnaire, and the MSDQ. Findings indicate strong internal consistency, reliability, incremental validity, and predictive validity of the instrument, indicating the superiority of the MSDQ's ability to predict sexual abuse compared to physical abuse or the loss of a family member. It is concluded that the MSDQ can be integrated into the evaluation process performed by healthcare professionals in the diagnosis of minors with unexplained symptomatology.